FORMATION AND PROPERTIES OF CARBON IN POROUS SPACE OF SILICA-ALUMINA CERAMICS (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
By using of XRD, IR, SEM methods and microanalysis, it was investigated the process of carbon formation during thermo destruction of sucrose inside pores of silica-alumina ceramics in conditions of oxygen deficient. It was found that for carbon formation inside pores, temperature treatment of sucrose must be 600oC and time of heating 15 min. At such regime of carbonization, carbon material is produced in the form of islets on the surface of pores and in the form of spherical particles of different sizes.Â  Carbon particles present a set of aggregates from chaotic graphene clusters. On surface of carbon particles is formed grapheme oxide. Obtained results show that the carbonized ceramicsÂ  adsorbs in a good degree the dyes from water solution.